2000
DOI: 10.1017/s1357729800055168
|View full text |Cite
|
Sign up to set email alerts
|

Monthly variations in some reproductive parameters of Barki and Awassi rams throughout 1 year under subtropical conditions 1. Semen characteristics and hormonal levels

Abstract: Fifteen sexually mature rams, five each of Barki, Awassi (I, imported from Syria) and Awassi (LB, locally born in Egypt) were used in this study. Semen was collected monthly from rams for a period of 12 months to study semen characteristics. In addition, blood samples were collected from rams during the four seasons of the year to determine serum triiodothyronine (T3) and testosterone hormones. Results showed that Barki and Awassi (I and LB) rams are continuous breeders as they show sexual desire and produce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
9
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
7
9
0
1
Order By: Relevance
“…Blood TH concentrations were high in spring (increasing daylength) and low in autumn (decreasing daylength), which was not fully explained by the changes in environmental temperature (Figure 2; Buys et al, 1990;Todini et al, 1992; McMillen, 1995: Clariget et al, 1998;Rhind et al, 2000;Taha et al, 2000;Villar et al, 2000a;Merchant and Riach, 2002;Souza et al, 2002; Blaszczyk et al, 2004;Zamiri and Khodaei, 2005;Menegatos et al, 2006;Todini et al, 2006). It seems that when the temperature ranges are not extreme (mild climate, indoor housing, shelter in the night time), the effect of photoperiod and season-dependent TH profiles (mainly related to the daylength changes) are present.…”
Section: Season Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood TH concentrations were high in spring (increasing daylength) and low in autumn (decreasing daylength), which was not fully explained by the changes in environmental temperature (Figure 2; Buys et al, 1990;Todini et al, 1992; McMillen, 1995: Clariget et al, 1998;Rhind et al, 2000;Taha et al, 2000;Villar et al, 2000a;Merchant and Riach, 2002;Souza et al, 2002; Blaszczyk et al, 2004;Zamiri and Khodaei, 2005;Menegatos et al, 2006;Todini et al, 2006). It seems that when the temperature ranges are not extreme (mild climate, indoor housing, shelter in the night time), the effect of photoperiod and season-dependent TH profiles (mainly related to the daylength changes) are present.…”
Section: Season Effectsmentioning
confidence: 99%
“…In the Sahel desert, plasma T3 and T4 levels did not change significantly from the beginning of the cool season (December) until the end of the dry warm season (May), but a highly significant rise of both hormones was observed at the onset of the humid warm season (June) (Assane and Sere, 1990). It can be supposed that an enhanced thyroid activity during the humid warm season in such environments is functional for the animals facing the increased availability of food (quantity and quality), following the seasons characterised by food shortage.Blood TH concentrations were high in spring (increasing daylength) and low in autumn (decreasing daylength), which was not fully explained by the changes in environmental temperature (Figure 2; Buys et al, 1990;Todini et al, 1992; McMillen, 1995: Clariget et al, 1998;Rhind et al, 2000;Taha et al, 2000;Villar et al, 2000a;Merchant and Riach, 2002;Souza et al, 2002; Blaszczyk et al, 2004;Zamiri and Khodaei, 2005;Menegatos et al, 2006;Todini et al, 2006). It seems that when the temperature ranges are not extreme (mild climate, indoor housing, shelter in the night time), the effect of photoperiod and season-dependent TH profiles (mainly related to the daylength changes) are present.…”
mentioning
confidence: 99%
“…Many studies have shown that low content of seminal plasma proteins is associated with poor semen quality (White et al, 1987;Ashworth et al, 1994). Taha et al (2000) revealed that there was a positive relationship between semen quality and level of seminal plasma total proteins. Similar results were found by Osama and El-Sahn (2006), they found a positive relationship between increasing seminal plasma total proteins and albumin and increasing total number of sperm output.…”
Section: Seminal Plasma Characteristicsmentioning
confidence: 99%
“…The latitudinal location of the current experiment (33 • N) could be partly responsible for shifting the breeding season in summer rather than in autumn. A pronounced increase in testosterone level in spring and summer seasons has been recorded in studies conducted by Olster and Foster (1988) and Taha et al (2000). The previous authors suggested that in mature rams the stimulation of the hypothalamic-pituitary axis begins in spring when photoperiod increases.…”
Section: Discussionmentioning
confidence: 83%
“…This breed is well adapted to harsh environmental conditions and raised primarily for three types of products: meat, milk and wool (Iniguez and Hilali, 2009). Although seasonality pattern of Awassi rams has been previously reported (Taha et al, 2000;Kridli et al, 2007), little information is available about the seasonal profile of both testosterone and cortisol and the effects of electro-ejaculation and copulation process on Awassi rams. Therefore, the objectives of the current experiments were (1) to determine the seasonal pattern of testosterone and cortisol in Syrian Awassi rams during a period of 1 year and (2) to investigate electro-ejaculation and copulation effects on cortisol and testosterone levels during the breeding and non-breeding season.…”
mentioning
confidence: 99%